2015
DOI: 10.1159/000371818
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolic Risk in Patients Newly Diagnosed with Acromegaly Is Related to Fat Distribution and Circulating Adipokines and Improves after Treatment

Abstract: Background/Aims: Adipose tissue (AT) distribution is closely related to metabolic disease risk. Growth hormone (GH) reduces visceral and total body fat mass and induces whole-body insulin resistance. Our aim was to assess the effects of total and visceral AT (VAT) distribution and derived adipokines on systemic insulin resistance and lipid metabolism in acromegaly. Methods: Seventy adult patients with active acromegaly (43 males, age 49 ± 14 years) were evaluated before treatment, and a subset (n = 30, 20 male… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 38 publications
3
19
1
1
Order By: Relevance
“…Elevated IGF-I levels were associated with T2DM, independently of age and BMI. A number of metabolic parameters, such as fasting glucose, HbA1C and serum triglycerides, improved significantly during follow-up, confirming previous publications (41). Of note, mean BMI and body weight were higher at the last visit than at diagnosis, as reported elsewhere (42).…”
Section: Discussionsupporting
confidence: 88%
“…Elevated IGF-I levels were associated with T2DM, independently of age and BMI. A number of metabolic parameters, such as fasting glucose, HbA1C and serum triglycerides, improved significantly during follow-up, confirming previous publications (41). Of note, mean BMI and body weight were higher at the last visit than at diagnosis, as reported elsewhere (42).…”
Section: Discussionsupporting
confidence: 88%
“…For example, as TBS is computed from DXA images, any image "noise" can influence the TBS evaluation and excessive soft tissue in the abdomen, overlying the region of interest, may reduce the TBS estimate. It is known that with treatment of acromegaly, although BMI remains unchanged, the patients do accumulate fat, predominantly in the central depots (20,41), and this can interfere with TBS estimates and lead to a measurement of a false decrease in TBS.…”
Section: Discussionmentioning
confidence: 99%
“…Some technical limitations of TBS analyses should however be noted. Additional studies, both technical and clinical, should be performed to assess the advantages and limitations of the TBS in order to ensure that it is used appropriately, also in acromegaly, where the disease by itself, but also treatment will have major impact not only on bone tissue but also on surrounding tissue (20). In order to mitigate this problem in vivo, the TBS calculation is adjusted for BMI.…”
Section: Discussionmentioning
confidence: 99%
“…A hallmark of active acromegaly is an alteration of the distribution of the adipose tissue, mainly characterized by a decrease in fat mass, an increase in lean mass, and an ectopic extra-adipose tissue deposition [ 76 , 77 , 78 ]; such a condition determines an impaired insulin action in both hepatic and extra-hepatic tissues [ 79 ]. In this regard, Olarescu et al reported an elevated metabolic activity for adipose tissue in acromegaly, able to affect the production and the secretion of adipokines [ 76 , 77 , 78 ]. As for adiponectin, data are controversial in active acromegaly, as quoted above, but recently White et al proved the negative regulator effect of STAT5A transcription factor on the adiponectin expression in murine 3T3-L1 preadipocytes after GH treatment [ 80 ].…”
Section: Igf-1 and Adiponectin In Relation To Obesity Diabetes Amentioning
confidence: 99%